2018
DOI: 10.1186/s13046-018-0867-3
|View full text |Cite
|
Sign up to set email alerts
|

IL-6-mediated cross-talk between human preadipocytes and ductal carcinoma in situ in breast cancer progression

Abstract: BackgroundThe function of preadipocytes in the progression of early stage breast cancer has not been fully elucidated at the molecular level. To delineate the role of preadipocytes in breast cancer progression, we investigated the cross-talk between human breast ductal carcinoma in situ (DCIS) cells and preadipocytes with both an in vitro culture and xenograft tumor model.MethodsGFP or RFP was transduced into human DCIS cell line MCF10DCIS.com cells or preadipocytes using lentivirus. Cell sorter was used to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 34 publications
(36 reference statements)
1
25
0
1
Order By: Relevance
“…There are cancer-associated adipocytes (CAA) around breast cancer tissue. When adipocytes are co-cultured with breast cancer cells, the expression and secretion of IL-6 in adipocytes increase, promoting the invasion and migration of cancer cells [2527]. When IL-6R is blocked by anti-IL-6R antibody, the metastasis of breast cancer induced by IL-6 is reversed [28, 29].…”
Section: Caas Secrete Inflammatory Factors That Modify the Behavior Omentioning
confidence: 99%
“…There are cancer-associated adipocytes (CAA) around breast cancer tissue. When adipocytes are co-cultured with breast cancer cells, the expression and secretion of IL-6 in adipocytes increase, promoting the invasion and migration of cancer cells [2527]. When IL-6R is blocked by anti-IL-6R antibody, the metastasis of breast cancer induced by IL-6 is reversed [28, 29].…”
Section: Caas Secrete Inflammatory Factors That Modify the Behavior Omentioning
confidence: 99%
“…Adipocytes also play an active role in the TME and cancer-associated adipocytes have smaller lipid droplets and a more fibroblast-like phenotype, compared to normal adipocytes [ 140 ]. When preadipocytes were cocultured with breast cancer cells, there was enhanced CAF marker expression and IL-6 secretion, which promotes tumourigenesis; although the activation of Notch was not investigated [ 141 ]. RNA within exosomes released from stromal cells stimulated STAT1-dependent antiviral response signalling in breast cancer cells.…”
Section: Notch Signalling In the Tumour Microenvironment: Interactmentioning
confidence: 99%
“…The upgraded serum levels of leptin have also been associated with higher pathological grade and aggressive phenotypes in breast cancer patients [139]. Produced by adipose tissues, IL-6 is more secreted in CAAs compared with other adipocytes [131], and it has also been shown to promote cancer progression when adipocytes are co-cultured with breast cancer cells [140]. Furthermore, it has also been demonstrated that IL-6 production can regulate cancer cell survival, immune suppression and drug resistance by JAK phosphorylation and STAT3 activation [141].…”
Section: Cancer-associated Adipocytesmentioning
confidence: 99%
“…Pathobiology 2020;87:[125][126][127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142] …”
unclassified